Assessing visibility, legibility and comprehension for interactive whiteboards (IWBs) vs. computers. Issue 9 (20th October 2016) - Megalakaki, Olga; Aparicio, Xavier; Porion, Alexandre; Pasqualotti, Léa; Baccino, Thierry
Abstract : The usability of interactive whiteboards vs. computers was evaluated on three dimensions (visibility, legibility and comprehension) in the secondary school pupils. The visibility assessment consisted in detecting a visual stimulus varying in luminance using a staircase procedure, legibility was assessed with a target-search task, and we administered narrative and explanatory texts with or without illustrations to evaluate comprehension. The results of the visibility test showed that pupils found the light signal easier to detect on the IWB. For the legibility test, we observed differences in error rates and discriminability according to medium, font size and congruence between target and the distractor letters. Performances in the comprehension test were similar for both explanatory and narrative texts. Moreover, the presence of illustrations does not improve comprehension. These results could be related to the hierarchical structure of the texts, which facilitate comprehension.